Autonomic impairment and oxidative stress: Relationship in PCOS patients - Mostafa, Musfika; Ferdousi, Sultana; Sultana, Shamima; Akhter, Ayesha (Journal of Bangladesh Society of Physiologist, 2020)
Background: Polycystic ovary syndrome (PCOS) is one of the most common, heterogeneous endocrine disorder of reproductive aged women. Association of autonomic impairment and elevated oxidative stress may predispose these patients to increased cardiovascular risks. Objective: To evaluate the relationship between cardiac autonomic nerve function (CANF) and oxidative stress in patients with PCOS. Methods: This cross sectional study was conducted in Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from September, 2018 to August, 2019. For this study, 30 newly diagnosed PCOS patients aged 20-35 years were recruited and similar age, body mass index (BMI) 30 apparently healthy, regularly menstruating women were enrolled as control. CANF was assessed by analyzing time domain measures of Heart Rate Variability (HRV). HRV data were recorded by a digital data acquisition device, Powerlab 8/35 (AD instruments, Australia). For evaluation of oxidative stress, plasma catalase and plasma Malondialdehyde (MDA) levels were measured. Statistical analysis was done by unpaired “t” test and Pearson’s correlation test as applicable. Results: In this study, resting pulse rate, systolic blood pressure (SBP), diastolic blood pressure (DBP) were significantly higher (p<0.001, p<0.01, p<0.01 respectively) and standard deviation of the RR intervals (SDRR) (p<0.01), mean R-R interval, standard deviation of the difference between successive RR intervals (SDSD), square root of mean squared differences of successive RR intervals (RMSSD), proportion of RR interval with duration >50 ms (pRR50%) were significantly lower (p<0.001) in PCOS than healthy controls. In addition, plasma catalase was significantly lower (p<0.01) and plasma MDA was significantly higher (p<0.001) in PCOS patients compared to controls. On correlation analysis, mean heart rate, SDRR, SDSD, RMSSD and pRR50% showed negative correlation with plasma catalase and plasma MDA (p<0.05) in PCOS patients but these were not significant. Conclusion: The present study reveals that reduced parasympathetic activity in PCOS patients may be related to oxidative stress. J Bangladesh Soc Physiol. 2019, December; 14(2): 82-88